2015
DOI: 10.1186/s12876-015-0340-0
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast activation protein-α-expressing fibroblasts promote the progression of pancreatic ductal adenocarcinoma

Abstract: BackgroundPancreatic ductal adenocarcinoma (PDAC) is characterized by an extensive desmoplastic stromal response. Fibroblast activation protein-α (FAP) is best known for its presence in stromal cancer-associated fibroblasts (CAFs). Our aim was to assess whether FAP expression was associated with the prognosis of patients with PDAC and to investigate how FAP expressing CAFs contribute to the progression of PDAC.MethodsFAP expression was immunohistochemically assessed in 48 PDAC specimens. We also generated a fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(60 citation statements)
references
References 38 publications
1
58
0
1
Order By: Relevance
“…Interestingly, FAP protease-mediated remodeling of the tumor stroma was shown to promote tumor cell migration (26). Coculture of 3T3 fibroblasts forced to express FAP was demonstrated to increase invasive ability of pancreatic cancer cells (27). Collectively, these data suggest that FAP may regulate early steps of the metastasis cascade, i.e., tumor cell dissemination and/or invasion.…”
Section: Discussionmentioning
confidence: 95%
“…Interestingly, FAP protease-mediated remodeling of the tumor stroma was shown to promote tumor cell migration (26). Coculture of 3T3 fibroblasts forced to express FAP was demonstrated to increase invasive ability of pancreatic cancer cells (27). Collectively, these data suggest that FAP may regulate early steps of the metastasis cascade, i.e., tumor cell dissemination and/or invasion.…”
Section: Discussionmentioning
confidence: 95%
“…Fibroblast activation protein (FAP, also known as FAPa or seprase) is a 95‐kDa type II integral serine protease on cell surface and was identified in 1986 . FAP belongs to the post‐proline dipeptidyl aminopeptidase family, which have activities of dipeptidyl peptidase and gelatinase and can cleave amino‐terminal dipeptides between proline and other amino acids through formation of 170‐kDa by homodimerization .…”
Section: Discussionmentioning
confidence: 99%
“…Kawase et al confirmed the role of FAP in cancer cell invasion and EMT and additionally showed its role in the activation of cell cycle progression by phosphorylation of Rb protein in PDAC cells. They also demonstrated that TGF-β, which has been linked to induction of EMT, induces FAP expression [41]. …”
Section: Role Of Stromal Cells In Cancer Proliferation Progression mentioning
confidence: 99%